Green policies and leadership character: integrating pancasila, astha brata, and nature-inspired principles for sustainable futures - Fitriani, Arbania; Situmorang, Dominikus David Biondi; Ifdil, Ifdil (COUNS-EDU: The International Journal of Counseling and Education, 2024)
This study explores character-centric leadership, focusing on Pancasila and Astha Brata principles, to address global challenges like climate change. Using Kevin Cashman’s "Inside Out" approach, it examines how nature-inspired qualities—adaptability, cooperation, wisdom, and environmental respect—shape ethical leadership. Qualitative interviews with four experts highlight the integration of these values into leadership practices. Findings emphasize the importance of self-awareness, spiritual wisdom, and environmental ethics in fostering sustainable leadership. The research underscores the need for education systems to instill these values early, nurturing future leaders who prioritize humanity, diversity, and sustainability. This holistic approach aligns cultural values with modern leadership demands, offering solutions for complex global issues. The study also highlights the role of green policies and technological adaptation in addressing climate change. By combining Pancasila’s ethical framework, Astha Brata’s cultural guidance, and Cashman’s psychological insights, this research provides a comprehensive model for effective, value-driven leadership. These insights aim to inspire leaders to balance innovation with ecological responsibility, promoting long-term societal well-being.